LEISURE TIME AND ACTIVITY OF SENIORS AS EXEMPLIFIED BY THE CZĘSTOCHOWA CENTRE FOR SENIOR ACTIVITY - Nowińska, Monika; Bakota, Daniel (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Over the last quarter of a century the changing age structure in Poland could be observed. A significant part of the society is made up of seniors, which enforces senior policies whose mission is to provide model solutions to the problems of the elderly. A wide range of offers makes it possible to encompass any needs of the elderly in different aspects of their existence, including: health, activity/sport, managing leisure time and a number of areas concerning economic, social, cultural, and other problems in order to improve the quality of their lives. The ageing society results in the avalanche of needs, including those related to health. A person of advanced age becomes less efficient with health problems appearing on the physical and mental plane, which is associated with the financial burden of the State, queues in healthcare and many other, equally unpleasant effects. To a large extent, this could be prevented by providing the elderly help in maintaining physical fitness and mental well-being. The aim of this paper is to draw attention to the fact how the elderly manage their leisure time, which, at the same time, will be indicative of their needs in this respect. The examined group (50 people) are the elderly - women and men of different educational backgrounds, aged 60 or more who most often already have fixed income. From among these fifty, 25 people spend their leisure time in the Częstochowa Centre for Senior Activity, and the remaining 25 respondents - for comparison - are people who act on their own in order to fill their spare time for themselves. The method used for the survey was a diagnostic opinion poll, and the research tool - a questionnaire survey.